2021
DOI: 10.1038/s41598-021-83869-8
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic shape changes in newborns due to their position

Abstract: The highly compliant nature of the neonatal chest wall is known to clinicians. However, its morphological changes have never been characterized and are especially important for a customised monitoring of respiratory diseases. Here, we show that a device applied on newborns can trace their chest boundary without the use of radiation. Such technology, which is easy to sanitise between patients, works like a smart measurement tape drawing also a digital cross section of the chest. We also show that in neonates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
1
2
0
Order By: Relevance
“…Similarly to that observed by previous authors, 42,43 in our findings, both groups of infants showed a preponderant increase in latero‐lateral thoracic diameter over the antero‐posterior thoracic diameter from perinatal period to follow‐up. This finding was particularly evident in PE infants in whom the anteroposterior thoracic diameter showed a significantly reduced increase than controls from perinatal period to follow‐up, contributing to maintain an extrinsic cardiac compression.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly to that observed by previous authors, 42,43 in our findings, both groups of infants showed a preponderant increase in latero‐lateral thoracic diameter over the antero‐posterior thoracic diameter from perinatal period to follow‐up. This finding was particularly evident in PE infants in whom the anteroposterior thoracic diameter showed a significantly reduced increase than controls from perinatal period to follow‐up, contributing to maintain an extrinsic cardiac compression.…”
Section: Discussionsupporting
confidence: 92%
“…In a child with lower airway obstruction and increased respiratory effort, the peaks of pleural retraction can be appreciated both qualitatively and quantitatively. The first rib space above the diaphragm sees maximum negative pressure created by both the intercostal muscles and the diaphragm creating the ‘bucket‐handle’ motion of the ribs as the diaphragm contracts, 9 particularly in younger children with a pyramidal‐shaped chest 10,11 . As the pleural line slope is a sonographic representation of intercostal retractions, this area of the chest wall is the most likely to produce readily identifiable peaks and valleys on m‐mode tracing.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally the image reconstruction algorithm should use realistic patient specific models. This type of model preparation is obtainable using a combination of sensors like gravitation sensors [ 3 ] when measured superficially or via magnetic resonance imaging (MRI) or computed tomography (CT) scans. The required equipment to conduct the external detection is not often available and the latter cases become rare within the considered age group amid the vulnerability of infants to high radiation dosage in CT-scans [ 4 ] or necessity of sedation during MRI.…”
Section: Introductionmentioning
confidence: 99%